A Comprehensive Review of Drynaria quercifolia (L.) J. Sm - Mani, Kamalakkannan; Aiyalu, Rajasekaran; Thiruvengadarajan, V.S; Arivukkarasu, R; Suriyapriya, K (Pharmacognosy Reviews)
Drynaria quercifolia (L.) J. Sm is a young, fleshy rhizome can reach a maximum of 18 cm in length and 8 cm in width widely distributed throughout India, Malaysia, Southeast Asia, Indonesia, and Australia. It is traditionally used to treat pain, worm infections, skin ailments, fever, diarrhea, infertility and as an adjunct medication to treat diabetes. The evaluation of the phytochemical in different portions reported the existence of saponins, steroids, triterpenoids, phenolic compounds, alkaloids, flavonoids and tannins. According to pharmacological reports, it has antimicrobial, anti-inflammatory, antioxidant activity and anti-cancer properties. The current comprehensive review provides a summary of the pharmacological, phytochemistry, and traditional utilization of Drynaria quercifolia (L.) J. Sm as published in the literature. There are countless traditional uses for the herb Drynaria quercifolia (L.) J. Sm and it is also utilised in numerous folk treatments. To correlate this plant's traditional uses to the scientific literature that is available, a comprehensive review is thus necessary. There is a wide range of potential studies on this plant and investigations over a long period of time on its pharmacological effects, the discovery of potential lead compounds, and the standardization of different plant parts to prevent adulteration.
Keywords: Drynaria quercifolia (L.) J. Sm; Phytochemistry; Pharmacognosy; Pharmacology; Traditional uses